Empirical data demonstrates risk-tradeoffs between landscapes for herbivorous fish may promote reef resilience. (February 2018) - Fong, Caitlin R.; Frias, Matthew; Goody, Nicholas; Bittick, Sarah Joy; Clausing, Rachel J.; Fong, Peggy
Abstract: Herbivores balance resource requirements with predation risk, which can differ among landscapes; hence, landscape can shape these trade-offs, influencing herbivore distribution and behavior. While this paradigm has been well established on coral-dominated reefs, tropical reefs worldwide are shifting to algal dominance. If herbivores avoid algae due to higher risk and forage in coral, these algal states may be stabilized. However, if herbivores forage more in resource-rich algal states, this may promote coral recovery. We assessed the distribution and behavior of herbivorous fishes in Moorea, French Polynesia in coral and algal turf-dominated fringing reef sites. Acanthuridae were more abundant in coral states and Labridae, tribe Scarinae, in algal turf states, though total fish abundances were equivalent in the two states. Fish in both families spent more time feeding in algal states and hiding/swimming in coral states. Thus, behavior reflects the trade-off between resource acquisition and refuge in these two landscapes and may promote recovery to coral. Graphical abstract: Highlights: Landscape can shape these trade-offs between predation and resource availability. This can feed back to community state on coral reefs and may promote recovery. Fish spent more time feeding in algal states and hiding/swimming in coral states. Thus, behavior reflects trade-off between resources and may promote recovery.